168k views
1 vote
(9+q)(8-q)= polynomial in standard form

1 Answer

2 votes

Answer:

- q² - q + 72

Explanation:

To express the given expression as a polynomial in standard form, we would first multiply the individual elements in one parenthesis with the elements in the second.

We would then rearrange the outcome and simplify it algebraically.

The arrange it in the order of the unknown variable.

As such,

(9+q)(8-q) = 9(8-q) +q(8-q)

= 72 -9q + 8q - q²

= 72 - q - q²

= - q² - q + 72

User Teemu
by
4.6k points